The Effectiveness Of Qanun Aceh No. 6/2014 Of Jinayat Law In Order To Prevent Jinayah Khalwat In Law Territory Of Sabang Municipality - Webby Aditya (Faculty of Law, Andalas University, 2018)
Article 23 paragraph (1) of Aceh Islamic Criminal Law No 6 of 2014 tells about Indecency (Jinayat) law which regulates the criminal punishment for the perpetrator of jarimah khalwat. This article is expected can minimize the crime rate of the indecent (jinayah) behavior perpetrator. However, in fact the number of jarimah khalwat perpetrator increase steadily as what happened in Sabang Municipality law area. It proves that there were two legal issues, what is the causes of the ineffectiveness of the indecency (jinayat) law in minimizing the number of jinayat perpetrator in Sabang Municipality? This research was aimed to know the obstacle of the increasing jinayat khalwat issue which make jinayat law become ineffective in minimizing jinayat khalwat perpetrators in Sabang Municipality, and to know the efforts conducted by the Civil Service Police Unit, Sharia Policy, and Office of the District Prosecutor General of Sabang Municipality and to know the factor which causes the number of jinayah khalwat perpetrator in Sabang Municipality. The research method used in this research was empirical juridical empirical using case approach, historical approach, comparative approach, conceptual approach, and statute approach). The research result shown that there were 3 effectiveness obstacle factors of jinayat law in Sabang Municipality, the first obstacle of jinayat law is the bad regulation because the punishment is an alternative not a cumulative and for those who deal with the jinayat law is potentially punished with canning punishment in public, the application of jinayat law normatively is in contrary with the basis of personality and territoriality which causes this law contrary with the fair legal system (due process of law). The second factor which becomes the obstacle related to quality and quantity of the human resource of the law enforcement, law understanding and the number of personnel investigator of the Civil Service Police Unit and Sharia Police of Sabang Municipality was limited. The third factor, there is no special jinayah prison cell in the Civil Service Police Unit and Sharia Police of Sabang Municiplaity